Effect of chlorhexidine on bond strength of two-step etch-and-rinse adhesive systems to dentin of primary and permanent teeth - Ricci, Herica Adad; Sanabe, Mariane Emi; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Mosher & Linder, Inc, 2010)
Purpose: To evaluate the influence of chlorhexidine digluconate (CHX) application on the immediate microtensile bond strength (mu TBS) of two-step etch-and-rinse adhesive systems to the dentin of primary and permanent teeth. Methods: Noncarious human teeth (24 primary molars and 24 premolars) were used. The primary and permanent teeth were randomly assigned to three groups (n = 8) according to the adhesive system: Adper Single Bond, Prime & Bond NT and Excite DSC. Each group was further divided in two subgroups (n = 4) in which the phosphoric acid-etched dentin was treated with 20 mu L of either 2% CHX or deionized water for 60 seconds prior to adhesive system application. The adhesive systems were applied according to the manufacturers' instructions and resin composite blocks were built up on the treated surfaces. The teeth were vertically sectioned perpendicular to adhesive interface and beam-shaped specimens with a 0.81 mm(2) cross-sectional area were obtained and subjected to mu TBS testing at a crosshead speed of 0.05 mm/minute. mu TBS data were analyzed statistically by ANOVA and Tukey's test (alpha = 0.05). The failure modes were verified with a stereomicroscope. Results: CHX application increased significantly (P < 0.05) the mu TBS of Prime & Bond NT and Single Bond to the acid-etched primary and permanent dentin, while no positive or negative effect was observed for Excite DSC. There was a predominance of adhesive failures in all control and CHX-treated groups. No fracture distribution pattern was observed. (Am J Dent 2010;23:128-132).